Gradients In Success: The Impact of Wave Energy, Elevation and Predation on Oyster Reef Restoration - Albright, Anna (East Carolina University, 2022)
The structure of coastal communities varies spatially and temporally in response to abiotic and biotic stressors. Local environmental conditions can be modified by the presence of a foundation species, whose dominant physical presence facilitates the growth of other organisms by ameliorating stress, providing settlement substrate and increasing resources. Oyster reefs (Crassostrea virginica) are an important foundation species found in estuarine environments. Oyster reefs form three-dimensional, structurally complex, biogenic habitats, that modify sediment and wave dynamics and ameliorate stress for community associates. Furthermore, they also act as a form of green-infrastructure, decreasing erosion rates and preventing shoreline loss. Because of their numerous benefits, efforts have been made to restore oyster reefs globally, with varying levels of success. Variability in the success of these restoration projects may be due to a lack of understanding of the abiotic and biotic factors that govern reef ecology. To better understand how abiotic and biotic processes regulate intertidal oyster reef community structure and their effects on restoration, we investigated the following research questions: 1) How does wave energy below 500 J/m affect oyster abundance? 2) How does reef crest height affect oyster abundance? 3) How does wave energy mediate oyster consumption? 4) How does reef relief mediate consumption of oysters? Oyster breakwaters of two different reliefs (high vs. low) were constructed to assess how reef relief affects oyster abundance. Wave gauges were built and deployed to monitor the local wave energy environment at each site. A manipulative field experiment was used to quantify consumption with different relief and caging treatments. Results suggest that constructing reefs with high vertical relief significantly increases oyster abundance. However, the interaction between reef crest elevation and wave energy can modify this relationship, causing site-level differences in oyster abundance. Furthermore, juvenile oyster consumption was not dictated by relief and instead was site specific, most likely due to differences in predator identity at each site. This suggests that when reefs attain high oyster densities, they can support numerous community associates. The accumulation of high oyster densities on an alternative reef material, like OysterCatcher(TM) material, suggests that this substrate is suitable for future oyster restoration projects. However, practitioners and researchers must be aware of the effects of environmental factors such as wave energy when restoring reefs. Further research is needed to understand how human changes to the environment, such as altered wave energy due to high boating traffic, interacts with design characteristics and reef ecology to impact restoration successes and failures.
Keywords: oyster reef; wave energy; elevation; predation; reef height; Reef ecology; Restoration ecology; American oyster